Development of a Fleet Management System Application: A Design Thinking Approach at a Property Company - Muji Rahmad; Astri Ghina (International Journal of Applied Business and International Management, 2025)
The advancement of digital technology has become a crucial strategy for businesses, including Telkom Property, which operates in the fleet management industry. The company faces challenges related to cost efficiency, time efficiency, and security. This study aims to analyze the requirements for implementing a fleet management system application using the design thinking approach to support the company’s efficiency programs. The design thinking methodology employed consists of five stages: (1) empathize, (2) define, (3) ideate, (4) prototype, and (5) testing. Data were collected through interviews with eight respondents, comprising five external and three internal stakeholders. The 635 method was used to prioritize ideas for prototype development. The prototype, presented as a fleet management application mockup, was tested with respondents to ensure feature alignment with user needs. The study findings reveal that the developed fleet management system application enhances efficiency, security, and user satisfaction. Application evaluation using the System Usability Scale (SUS) yielded a score of 78.4, surpassing the threshold of 71.1. Additionally, 100% of respondents agreed that the application meets their expectations. This research concludes that implementing a fleet management application based on the design thinking approach is effective in supporting Telkom Property's operational efficiency